Ordinance no. 1, § 6, in THE MINING ECHO, Jul. 7, 1877, at 1 - (:unkn) unknown (My University, 1870)
Any person who shall carry any concealed pistol, dirk, or other deadly weapon, within the limits of the- city, shall he deemed guilty of a misdemeanor, and upon conviction thereof, be fined in a sum not less than $10 nor more than $50.
Keywords: CARRY - CONCEALED